2020
DOI: 10.5306/wjco.v11.i7.412
|View full text |Cite
|
Sign up to set email alerts
|

Role of imaging biomarkers in mutation-driven non-small cell lung cancer

Abstract: Lung cancer remains the leading cause of cancer-related deaths worldwide. The treatment of non-small cell lung cancer (NSCLC), which accounts for a vast majority of lung cancers, has shifted to personalized, targeted therapy following discoveries of several targetable oncogenic mutations. Targeting of specific mutations has improved outcomes in many patients. This success has led to several target-specific agents replacing chemotherapy as first-line treatment in certain mutated NSCLC. Several researchers have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…In a parallel vein, Zhou et al [133] found that when radiomic features are amalgamated with machine learning methodologies, there is a powerful discriminatory capacity to distinguish between primary lung lesions and metastatic lung lesions in the brain. Intriguingly, emerging datasets also indicate that NSCLCs harboring different targetable oncogenic driver mutations (e.g., ALK) present unique imaging features, both in the primary tumor and in metastatic tumors [134,135]. Specifically, the utility of contrast-enhanced T1-weighted (CET1W) images in predicting EGFR mutation status in small-sized brain metastases (<10 mm) from lung cancer has been highlighted [136].…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…In a parallel vein, Zhou et al [133] found that when radiomic features are amalgamated with machine learning methodologies, there is a powerful discriminatory capacity to distinguish between primary lung lesions and metastatic lung lesions in the brain. Intriguingly, emerging datasets also indicate that NSCLCs harboring different targetable oncogenic driver mutations (e.g., ALK) present unique imaging features, both in the primary tumor and in metastatic tumors [134,135]. Specifically, the utility of contrast-enhanced T1-weighted (CET1W) images in predicting EGFR mutation status in small-sized brain metastases (<10 mm) from lung cancer has been highlighted [136].…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…Molecular markers have become increasingly important in the era of personalized medicine (67). Lung cancers with certain biomarkers have been found to respond favorably to targeted therapies, thereby directing treatment strategies (68). However, biomarker profiles and targeted therapies are beyond the scope of this chapter as they play a lesser role in the management of small lung nodules, most of which will be surgically treated.…”
Section: Biomarkers and Personalized Medicinementioning
confidence: 99%
“…Imaging can also be used to detect lung cancer specific features within the tumor and metastatic patterns which are correlated to the common driver mutations [5]. While there is not enough evidence for imaging biomarkers to be used on their own for prognostic or therapeutic purposes, they may be useful in localizing tumor tissue during intervention.…”
Section: Introductionmentioning
confidence: 99%